Economic Growth and Equality in Reducing Poverty - Muttaqin, Zaenal (Signifikan: Jurnal Ilmu Ekonomi, 2012)
In some developing countries, the instrument to alleviate the poverty is by using the economic growth. So, the increasing in investment, infrastructure development, and macroeconomics stability always be priority from developing countries. In this article explain that economic growth is not the important factor to alleviate the poverty, because equality sometimes is more important rather than the economic growth. In this context, its measure by inequality growth trade off index (IGTI). This method is to measure the influence of economic growth to reducing the inequality, with this method every country can measure which one is better to reducing the poverty whether the economic growth or equality. With this method, Laos in 2000 show that economic growth is more important than equality, but in the same year in Thailand show that equality is more important than economic growth.DOI: 10.15408/sjie.v1i1.2592